2020
DOI: 10.1111/vco.12632
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating optical coherence tomography for surgical margin assessment of canine mammary tumours

Abstract: Optical coherence tomography (OCT) uses near-infrared light waves to generate real-time, high-resolution images on the microscopic scale similar to low power histopathology. Previous studies have demonstrated the use of OCT for real-time surgical margin assessment for human breast cancer. The use of OCT for canine mammary tumours (CMT) could allow intra-operative visualisation of residual tumour at the surgical margins. The purpose of this study was to assess OCT imaging for the detection of incomplete tumour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Surgery is the primary treatment in the control of CMTs; the goal is to remove the tumor(s) with clean margins and, depending on the case, to prevent the development of new tumors in the remaining glands ( 4 ). Clean margins have been found to be predictive of the median survival time (MST) in dogs with stages I–III ( 19 ), and very recent publications have elucidated new strategies for the intraoperative assessment of margins using near-infrared light waves to generate real-time, high-resolution images on the microscopic scale, similar to low-power histopathology ( 47 49 ).…”
Section: Conventional and New Clinical And Histological Approachesmentioning
confidence: 99%
“…Surgery is the primary treatment in the control of CMTs; the goal is to remove the tumor(s) with clean margins and, depending on the case, to prevent the development of new tumors in the remaining glands ( 4 ). Clean margins have been found to be predictive of the median survival time (MST) in dogs with stages I–III ( 19 ), and very recent publications have elucidated new strategies for the intraoperative assessment of margins using near-infrared light waves to generate real-time, high-resolution images on the microscopic scale, similar to low-power histopathology ( 47 49 ).…”
Section: Conventional and New Clinical And Histological Approachesmentioning
confidence: 99%
“…To date, OCT imaging has been evaluated in a limited capacity for surgical margin assessment in dogs. 5,21,22,40,41 Initial studies demonstrated differences in microstructural appearance and textural characteristics of different tissues at surgical margins. 5,21,22,40,41 The microstructural features were used to train observers of different specialties (radiology, pathology, surgery and OCT imaging) in a recent study.…”
Section: Discussionmentioning
confidence: 99%
“…5,21,22,40,41 Initial studies demonstrated differences in microstructural appearance and textural characteristics of different tissues at surgical margins. 5,21,22,40,41 The microstructural features were used to train observers of different specialties (radiology, pathology, surgery and OCT imaging) in a recent study. 40 Observers showed good accuracy of interpretation for ex vivo images, with an overall sensitivity of 83% and specificity of…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, OCT usually operates in reflection mode, and is well suited to imaging thick tissue specimens. OCT has shown potential in label-free tissue block imaging 11 , 24 , surgical margin assessment 25 , 26 , and biopsy examination 27 , 28 . However, OCT uses optical scattering contrast which highlights predominately morphological information.…”
Section: Introductionmentioning
confidence: 99%